Effective and Equitable Teacher Practice in Mathematics and Science Education: A Nordic Perspective Across Time and Groups of Students - Teig, Nani; Nilsen, Trude; Yang Hansen, Kajsa (IEA Research for Education, 2024)
This open access book presents original research on effective and equitable teacher practice in mathematics and science education across Nordic countries. It focuses on three key aspects of teacher practice: what teachers teach, how teachers teach, and how teachers assess their students. To provide a comprehensive understanding of teacher practice, data from the IEA’s Trends in Mathematics and Science Study (TIMSS) from 2011 to 2019 was analyzed. TIMSS provides large-scale and representative data, allowing an in-depth investigation of the relations between teachers, their practices, and student outcomes. The findings highlight the changes in teacher practice over time and the extent to which such changes explain the differences in student outcomes. This research also contributes to understanding how the relationships between teacher practice and student outcomes vary across different student groups (i.e., gender, socioeconomic status, and language background). The empirical evidence presented not only adds a significant layer to the academic discourse but also offers practical implications. These insights are crucial in facilitating educational policymaking and classroom practices aimed at improving student outcomes and closing gaps in educational inequality.